Hadith #2718 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Auf bin Malik al-Ashja'i; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي (Sunan Abi Dawud)
Anas reported the Apostle of Allaah(ﷺ) as saying “He who kills and infidel gets his spoil.” Abu Talhah killed twenty men that day meaning the day of Hunain and got their spoils. Abu Talhah met Umm Sulaim who had a dagger with her. He asked “What is with you, Umm Sulaim”? She replied “I swear by Allaah, I intended that if anyone came near me I would pierce his belly with it. Abu Talhah informed the Apostle of Allaah(ﷺ)about it. Abu Dawud said “This is good (hasan) tradition.” Ab
Grade: Sahih

Hadith #2719 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Auf bin Malik al-Ashja'i; Jubayr bin Nufayr al-Hadrami; Khalid bin Ma'dan خالد بن معدان; Nufayr bin Malik al-Hadrami; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
‘Awf bin malik Al Ashja’I said “I went out with Zaid bin Harith in the battle of Mutah. For the reinforcement of the Muslim army a man from the people of Yemen accompanied me. He had only his sword with him. A man from the Muslims slaughtered a Camel. The man for the reinforcement asked him for a part of its skin which he gave him. He made it like the shape of a shield. We went on and met the Byzantine armies. There was a man among them on a reddish horse with a golden saddle and golden we
Grade: Sahih

Hadith #2720 - Sunan Abi Dawud - Auf bin Malik al-Ashja'i; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Khalid bin al-Walid; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by ‘Awf bin Malik Al Ashja’I through a different chain of narrators.
Grade: Sahih

Hadith #3664 - Sunan Abi Dawud - Aabad bin 'Aabad bin Habib عباد بن عباد بن حبيب بن المهلب; Abdul A'ala bin Mushir al-Ghasani عبد الأعلى بن مسهر أبو مسهر الغساني; Auf bin Malik al-Ashja'i; Mhmwd bin Khalid محمود بن خالد; Yahya bin Abi 'Amr يحيى بن أبي عمرو السيباني (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone acquires knowledge that should be sought seeking the Face of Allah, but he acquires it only to get some worldly advantage, he will not experience the arf, i.e. the fragrance, of Paradise.
Grade: Sahih

Hadith #4998 - Sunan Abi Dawud - Abdullah bin al-'Ala' عبد الله بن العلاء بن زبر; Abu Idrees al-Khulani أبو إدريس الخولاني; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Auf bin Malik al-Ashja'i; Bsr bin 'Ubaidullah بسر بن عبيد الله الحضرمي; Mu'ml bin al-Fadl مؤمل بن الفضل (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and said: Messenger of Allah! give me a mount. The Prophet (ﷺ) said: We shall give you a she-camel’s child to ride on. He said: What shall I do with a she-camel’s child? The Prophet (ﷺ) replied: Do any others than she-camels give birth to camels?
Grade: Sahih

Hadith #5147 - Sunan Abi Dawud - al-Nhas bin Qhm al-Qaysy Abu النهاس بن قهم; Auf bin Malik al-Ashja'i; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Shdad bin 'Abdullah شداد بن عبد الله القرشي أبو عمار; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone cares for three daughters, disciplines them, marries them, and does good to them, he will go to Paradise.
Grade: Hasan